Inhibition of Nitric Oxide Production in Activated Macrophages Caused by Toxoplasma gondii Infection Occurs by Distinct Mechanisms in Different Mouse Macrophage Cell Lines - Cabral, Gabriel R. de Abreu; Wang, Zi T.; Sibley, L. D.; DaMatta, Renato A. (Frontiers in Microbiology, 2018)
Toxoplasma gondii, the causative agent of toxoplasmosis, is a widespread intracellular parasite able to infect virtually any nucleated cell. T. gondii infection of activated macrophages inhibits nitric oxide (NO) production; however, parasite effector responsible for this block has not been defined. Macrophage populations are extremely heterogeneous responding differently to stimuli, and to parasite infection. Here we evaluated the inhibition of NO production caused by T. gondii infection of J774-A1 and RAW 264.7 macrophages and assessed the role of several known parasite virulence factors in this phenotype. Infection of activated macrophages from both macrophage lines reduced NO production, however the mechanism of this decrease was different. Consistent with previous reports, infected J774-A1 macrophages had reduced iNOS expression and lower number of iNOS positive cells. In contrast, T. gondii infection of RAW 264.7 macrophages did not alter iNOS expression or the number of iNOS positive cells, and yet it led to lower levels of NO production. Deletion of a number of previously defined virulence factors including ROP kinases that disrupt innate immune factors, TgIST which blocks STAT1 activation, as well as the secretory trafficking proteins ASP5 and MYR1, did not alter the phenotype of decreased NO production. Taken together our findings indicate that T. gondii infection inhibits NO production of activated macrophages by different mechanisms that involve reduction of iNOS expression vs. iNOS impairment, and suggest that a novel parasite effector is involved in modulating this important host defense pathway.